Respuesta :
Answer:
- f−1=log3x. Explanation: y=3x ⇒log3y=log3(3x) (logarithms of both side are equal) ⇒x=log3y ⇒f−1=log3x.Step-by-step explanation:
The one that is an the inverse of y = 3 Superscript x is y = 3x is f-1(x) = 1/3x.
What is the inverse about?
The use of the idea of inverse function to look for the solution is given below:
Note that, y = 3x
Then let f(x) = y = 3x
One will need to Switch x and y and as such, x = 3y
Then one should express y in terms of x and as such, y = 1/3 x
Since f(x) = y ⇒ x = f-1(y)
Then f-1(y) = 1/3x
Therefore, the inverse of y = 3x is f-1(x) = 1/3x.
Learn more about Inverse Function from
https://brainly.com/question/3831584
#SPJ9